PHRASEOLOGICAL EXPRESSIONS WITH THE COMPONENT ‘SHOES’ IN THE LINGUOCULTURAL PICTURE OF THE CHINESE WORLD - Ma Guangdong (Russian Studies in Culture and Society)
The study of phraseological expressions with the component “shoes” in Chinese language and culture involves an in-depth study of the rich connotation and meaning of this unique cultural symbol. Phraseologisms, as treasures of the Chinese language, are not only the historical heritage, but also the wisdom and emotions of the nation. “Shoes”, being an indispensable item in daily life, shows a special style in phraseological expressions, and its unique status cannot be ignored.